Voltage stability assessment for solar photovoltaic penetration using Reactive Power–Voltage and Active Power–Voltage modal analysis - M.H. Ibrahim; S.P. Ang; M.N. Dani; Rafidah Petra; M.A. Salam (Energy Reports, 2023)
The assessment of voltage stability in a power system is crucial to ensure all buses in the network can maintain the desired voltage or avoid maximum loadability when subjected to load disturbance. Current research has tended to concentrate on developing new voltage stability assessment tools rather than identifying the best location for the penetration of solar photovoltaic (SP) generation in the network. This paper examines and evaluate the power systems voltage stability with increasing SP penetration levels by employing both the Active Power–Voltage (PV) and Reactive Power–Voltage (QV) modal analysis. The effect of load flow study by penetrating SP at the weakest and the strongest load bus has been investigated in this work. Furthermore, the analysis in this work was carried out in the modified Brunei Darussalam Department of Electrical Services (DES) power system. The main contribution of this paper is to assess and identify the best and worst locations for SP penetration in the simplified DES power system network in Brunei Darussalam using both the QV and PV modal analysis. The load flow results show that the penetration of SP generation is much better at the strongest bus due to it does not influence other load buses as compared to the least reliable bus in the network.